Becoming nobody [videorecording (DVD)] - Catto, Jamie; Forster, Alex (Love Serve Remember Foundation, 2020)
Ram Dass shares the essence of his core wisdom through his iconic humor, joy, and honesty. Historical footage compliments an engaging conversation with director Jamie Catto as they explore the life experiences that helped to free Ram Dass from the attachment to his "somebody-ness" a journey that transformed him into the radiant soul who now inspires a new generation. It is the quintessential portal to Ram Dass' life and teachings